If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 61 = 16 + 5(x + -3) Reorder the terms: 61 = 16 + 5(-3 + x) 61 = 16 + (-3 * 5 + x * 5) 61 = 16 + (-15 + 5x) Combine like terms: 16 + -15 = 1 61 = 1 + 5x Solving 61 = 1 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 61 + -5x = 1 + 5x + -5x Combine like terms: 5x + -5x = 0 61 + -5x = 1 + 0 61 + -5x = 1 Add '-61' to each side of the equation. 61 + -61 + -5x = 1 + -61 Combine like terms: 61 + -61 = 0 0 + -5x = 1 + -61 -5x = 1 + -61 Combine like terms: 1 + -61 = -60 -5x = -60 Divide each side by '-5'. x = 12 Simplifying x = 12
| 4.2q-5.9-5.5q=-2.3q-3.6 | | 8p=2(p+9) | | 8(w-2)= | | 100.39=28.90+49.99+2x | | (2x+5)+(x-2)= | | a+(a+450000)=625000000 | | 38.5=2x-1.5+2x-1.5+x+x+x+7.2 | | 33.9ab-82.4ac+29.3ad-84.8ac+73.2ab= | | y-17=-33 | | 2x-20=36.37 | | 9.9x+38.57=-10.1+38.41b | | 108=x+x+3.5x+3.5x | | Y^2+2y-24=0 | | 66.8=2x+4.7+2x+4.7+2x+4.7+2x+4.7 | | (c-3)(c-3)=o | | x+4=9x-72 | | 9(3+x)= | | 27y^2-52y+25= | | 66.8=2x+4.7 | | 5p-(4p-4)=17 | | 19.8=x+2.9+4.5+x | | 9.9x+38.57=-10.1+38.41 | | 15(x+1)=5(4x) | | y=zr | | p=0.4+-350.002x | | 2w^9-20w^8-48w^7= | | p=1.4+-350x-1+-0.002x | | 1(t-4)+7t=4(2t+3)-8 | | 15x+15=20x | | p(x)=-0.002x^2+1.4x-350 | | 7.4x-2.9=11.9 | | 1.95x-4.38z+2.83a-5.21z-9.27x= |